The credibility and usefulness of the chairman's statement: institutional investors' perceptions / Anita Jamil, Hamidah Bani and Yang Chik Johari - Jamil, Anita; Bani, Hamidah; Johari, Yang Chik (2005)
The purpose of this paper is to identify the credibility and usefulness of the Chairman's Statement from the institutional investors' perceptions. This paper investigates the important elements to be incorporated into a Chairman's Statement from the investors' perception. The research questionnaire has been distributed to institutional investors all over Malaysia. Institutional investors consist of the fund managers of banks, government bodies, insurance companies, investment trusts and pension funds. The results indicate that Chairman's Statement is an important item in the annual report and useful tool for institutional investor in investment decision making. Generally, the institutional investor perceives confidence on the information provided in the Chairman's Statement reported in the Annual Report. The result can be concluded that financial performance, profitability and business strategies should be incorporated into chairman's statement.